A Differential Study into Body Fat in Healthy and Hypertensive Populations Using Multiple Indexes - Wang R (Dove Medical Press, 2021)
Ran Wang,1 Qiuzhen Wang2 1Department of Clinical Nutrition, Weifang People’s Hospital, Weifang 261041, People’s Republic of China; 2Department of Public Hygiene, Qingdao University, Qingdao 266021, People’s Republic of ChinaCorrespondence: Qiuzhen WangDepartment of Public Hygiene, Qingdao University, No. 38 of Dengzhou Road, Shibei District, Qingdao 266021, People’s Republic of ChinaTel/Fax +86 0532 8299 1011Email wangqiuzhen1234@163.comObjective: The present study aims to investigate the difference in body fat in healthy and hypertensive populations with the use of five evaluation indexes.Methods: A total of 895 healthy subjects, who underwent physical examination and body composition analysis in the Physical Examination Center of Weifang People’s Hospital from January 2016 to January 2017, were selected as the study subjects. Among these subjects, 527 were male and 368 were female, and their age ranged from 18 to 60 years, with a mean age of 43.12 ± 9.34. They were divided into four groups, according to their blood pressure and biochemical examination results, a male healthy male group, a hypertensive male group, a healthy female group and a hypertensive female group. Their height, weight, waist and hip circumference were measured, and their body composition was analyzed to obtain data for body fat percentage and visceral fat area. The data and indexes were statistically analyzed using SPSS 18.0 statistical software, and P< 0.05 was considered to be statistically significant.Results: The difference in body mass index (BMI) between the healthy population and the hypertensive population was statistically significant (P< 0.05). The difference in waist circumference between the healthy male group and the hypertensive male group was statistically significant (P< 0.05). The difference in waist-to-hip ratio between the healthy population and hypertensive population was statistically significant (P< 0.05). The difference in body fat percentage and visceral fat area between the healthy population and hypertensive population was statistically significant (P< 0.05).Conclusion: The five indexes, namely the BMI, waist circumference, waist-to-hip ratio, body fat percentage, and visceral fat area, demonstrated statistically significant differences between the healthy population and the hypertensive population. However, since the evaluation results of some of the indexes also differed from available critical values, further validation is necessary.Keywords: body mass index, waist circumference, waist-hip ratio, body fat percentage, visceral fat area, bioimpedance